Al-Kifayat Al-Mihaniyyah al-Lazimah Li Mudiri Madaris al-Ta’lim al-Asasi Bi Muhafazah Dhofar - Professional Competencies Required for Principals of Basic Education Schools in Dhofar Governorate - Suhail Salim, Aamri Ahmed; Sahrir, Muhammad Sabri (OCERINT International Organization Center of Academic Research, 2020)
This quantitative study discussed the professional competencies required for principals of basic education in Dhofar Governorate. The problem lies in the lack of training programs, and the need to enhance the knowledge, value, and skills dimensions. The study objective: was to determine the necessary professional competencies for principals of basic education schools in Dhofar Governorate. The researcher adopted the descriptive and analytical approach and a random sample of (75) principals were selected for basic education. The researcher designed a questionnaire to collect data, consisting of (46) statements distributed in three axes. The results of the study showed that social competencies came in first place with very high esteem, followed by educational competencies, while scientific competencies came third with high esteem.